Criminal investigation and forensic tools for smartphones. (7th August 2009) - Jahankhani, Hamid
The technological capability of mobile devices, in particular Smartphones, makes their use valuable to the criminal community as a data terminal in the facilitation of organised crime or terrorism. The provision of best evidence admissible in a Court of Law requires a thorough understanding of the legal precepts of law under which such admissible evidence may be obtained and proffered. Equally, in the digital age, this evidence must be obtained and presented in a manner which not only ensures admissibility but is also irrefutable. The paper is a technical overview of the currently available forensic software tools that are developed to carry out forensic investigation of mobile devices and terminal/device examination procedures.